Acute cortisol reactivity attenuates engagement of fronto-parietal and striatal regions during emotion processing in negative mood disorders. (November 2016) - Peters, Amy T.; Van Meter, Anna; Pruitt, Patrick J.; Briceño, Emily M.; Ryan, Kelly A.; Hagan, Melissa; Weldon, Anne L.; Kassel, Michelle T.; Vederman, Aaron; Zubieta, Jon-Kar; McInnis, Melvin; Weisenbach, Sara L.; et al.
Highlights: Cortisol predicted activation in several regions involved in emotion perception and control. Cortisol predicted hypoactivation of several of these regions in negative mood disorders. Cortisol may interfere with fronto-subcortical regulatory function in negative mood disorders. Abstract: Objective: Depression and bipolar disorder (negative mood disorders, NMD) are associated with dysregulated hypothalamic-pituitary-adrenal (HPA)-axis function and disrupted emotion processing. The neural networks involved in attenuation of HPA-axis reactivity overlap with the circuitry involved in perception and modulation of emotion; however, direct links between these systems are understudied. This study investigated whether cortisol activity prior to undergoing fMRI was related to neural processing of emotional information in participants with NMD. Methods: Forty-one adults ( M age  = 40.33, SD  = 15.57) with major depression (n = 29) or bipolar disorder (n = 12) and 23 healthy control comparisons ( M age  =  36 .43, SD  = 17.33) provided salivary cortisol samples prior to completing a facial emotion perception test during 3-Tesla fMRI. Results: Overall, pre-scan cortisol level was positively associated with greater engagement of the dorsal anterior cingulate (dACC), inferior parietal lobule, insula, putamen, precuneus, middle and medial frontal and postcentral gyri, posterior cingulate, and inferior temporal gyrus during emotion processing of all faces. NMD status moderated this effect; in NMD participants' pre-scan cortisol was associated with attenuated activation of the insula, postcentral gyrus, precuneus, and putamen for fearful faces and the medial frontal gyrus for angry faces relative to HCs. Cortisol-related attenuation of activation among NMD participants was also observed for facial identification in the dACC, putamen, middle temporal gyrus, precuneus, and caudate. Conclusions: Across all participants, cortisol was associated with greater activation in several regions involved in the perception and control of emotion. However, cortisol responsivity was associated with hypoactivation of several of these regions in the NMD group, suggesting that HPA-axis activity may selectively interfere with the potentially adaptive recruitment of circuits supporting emotion perception, processing and/or regulation in mood disorders.